(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the dangers arising from the incorrect interpretation of figurative (mutashabih) verses in the Holy Qurʼan and their impact on Islamic creed and society. The study analyzes how radical and deviant movements interpret Qurʼanic expressions only in their literal sense while rejecting the traditional scholarly methodologies of tafwid and taʼwil established by classical Sunni scholars. Special attention is given to theological issues such as tajsim (anthropomorphism), tashbih (likening Allah to creation), and extremist literalism. Through the analysis of selected Qurʼanic verses including “The Hand of Allah is above their hands” (al-Fath, 10), “Allah plotted” (Al ʿImran, 54), and the dialogue between Musa (peace be upon him) and Allah regarding seeing Him (al-Aʼraf, 143) the article demonstrates how classical scholars such as Ibn Kathir, al-Baydawi, al-Nasafi, and Fakhr al-Din al-Razi interpreted these verses within the framework of Arabic rhetoric, theology, and creed. The paper further discusses the misuse of figurative verses by extremist groups for political radicalization and takfir. It concludes that preserving sound Islamic belief requires adherence to the balanced methodologies of traditional Sunni scholarship, consideration of linguistic and historical contexts, and the strengthening of scholarly responses against superficial and extremist interpretations.